2011
DOI: 10.3109/13645706.2011.573797
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction after myomectomy: Comparison of patients with and without second-look laparoscopy

Abstract: Myomectomy is associated with a high risk of de-novo adhesion formation that may decrease fertility. The purpose of this study was to compare the reproductive outcome of patients after laparoscopic or open myomectomy who underwent second-look (SL) hysteroscopy and laparoscopy including adhesiolysis with patients with no SL intervention. A total of 170 patients underwent open or laparoscopic myomectomy at one centre. All patients were recommended SL. Reproductive results were analyzed in 12 and 24 months interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
1
10
0
1
Order By: Relevance
“…Although these prospective studies are among the largest reported, they did not consistently adjust for significant confounders such as age, infertility diagnoses, BMI, reproductive characteristics, anti-TPO antibodies, and anti-chlamydial antibodies. Different primary endpoints (clinical pregnancy, pregnancy loss, ongoing pregnancy, and live birth pregnancy) and inadequate sample sizes lend to difficulty in interpreting the variable results of prior studies (2, 14, 15, 1719). …”
Section: Discussionmentioning
confidence: 99%
“…Although these prospective studies are among the largest reported, they did not consistently adjust for significant confounders such as age, infertility diagnoses, BMI, reproductive characteristics, anti-TPO antibodies, and anti-chlamydial antibodies. Different primary endpoints (clinical pregnancy, pregnancy loss, ongoing pregnancy, and live birth pregnancy) and inadequate sample sizes lend to difficulty in interpreting the variable results of prior studies (2, 14, 15, 1719). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after abdominal myomectomy 89.29% of patients had de novo adnexal adhesions which might compromise fertility. In the laparoscopic group de novo adnexal adhesions were observed in 10.6% of patients [ 73 ]. Another study also assessed the occurrence of adhesions after laparoscopic myomectomy during a second procedure and found adhesions in only 1.6% of patients (2/121) [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 94.50% of them had abdominal and/or pelvic surgery. The risk of postoperative abdominopelvic adhesions following open surgery was found to be 34%, 8 40.6%, 9 and 50%. 10 In our study, the overall risk of adhesions was 45.1%.…”
Section: Discussionmentioning
confidence: 96%